The rate distortion region for coding in stationary systems - Sadeh, Ilan (Zielona Góra: Uniwersytet Zielonogórski)
We present the idea of process assignment as a basic tool to provide operational compression bounds. We give a simple proof for the operational rate distortion function using process assignment arguments for ergodic and stationary systems. We generalize the problem to multiterminal systems. A terse review of random process theory is followed by two examples in communications and computers industry, where this theory supplies key bounds to the network performance.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka